Komposisi Karawitan Tabuh Petegak Kreasi “Gacor" - I Kadek Putra Mahardika (GHURNITA: Jurnal Seni Karawitan, 2023)
Birds are one type of living creature that has a uniqueness that is widely respected by people. The uniqueness of the attractive shape, birds also have their own characteristics in addition to having physical beauty, birds are also able to make beautiful sounds. The beauty of the bird is like the sound of the bird, which has a very beautiful chirp so that it can attract people's attention to enjoy it. The characteristics of these types of birds, such as a melodious voice, a shrill voice and the chatter of the bird or what is often called “Gacor”. “Gacor” in addition to often sounding from the original sound can also vary the sound issued, which may imitate the sound of a bird that sounds like a bird. so that it adds to the attractiveness or beauty of the bird. Likewise in the musical work entitled “Gacor” as a form of clever rhythmic strains with various dynamics of the beauty of each note. By highlighting the agility of the kotekan played with bamboo gamelan, it is the hallmark of the work entitled “Gacor” so that the audience itself can feel the beauty, from the melodic strains, dynamics and rhythm of this work, which can cool a dynamically full heart.